Koneweczek osiem sztuczek i mycka aksamitna białogłowska. O dobrach doczesnych w inwentarzach rzeczy pozostałych po poznańskich mieszczanach - Banderowicz, Kinga (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The present article is meant to support the idea of the research methodological concept that underlies a diachronic approach to the study of the Polish language in the aim of providing appropriate methodological and practical tools for analyzing language change and the one that would include historical Polish language in the general study on the language. This, in turn, would create foundations for a better understanding of the linguistic phenomena occurring in more recent times. For the linguistic analyses, some sections of the archival municipal records of the city of Poznan have been selected: the inventories of Poznan’s burghers, whereas the longer passages have been excerpted from the local municipal records of the provincial court of justice, i.e., the records of civil litigation of the town’s board of aldermen. The source material, apart from being undoubtedly helpful in onomastic research, provides additionally an opportunity to learn more about the economic standing of the inhabitants, their professions and occupations and the related social standing. Thus obtained data make it possible to verify and, sometimes, reassess conclusions on thesocial stratification of the local townsfolk, the hierarchy in professions and, in addition, provide grounds for a reliable comparison of the degree and the growth rate in economic improvement between the burghers in Greater Poland and those of other towns and cities in Poland similar in size and importance. On the basis of the resulting lexical and semantic analyses one can conclude that townspeople from Greater Poland of the time were fairly well-off and enjoyed wealth in terms of having an abundance of material and worldly things. The contemporary measure of wealth was everyday consumer goods that featured household linen, table linen and clothing. Household items, such as kitchenware, tableware, bathroom accessories, goods for own use were also considered valuable. In addition, townspeople had also jewelry, real property or money, but these did not constitute any major determinant factors in determining a particular position in the hierarchy of social standing.